Indigenous Value Entrepreneurship Minang Communities as A Supplement to the Development of A Culturally Responsive Pedagogy - Hestiningtyas, Widya; Sinaga, Risma Margaretha (Journal of Economics Education and Entrepreneurship, 2024)
There have been many studies on entrepreneurship, but relatively few studies have revealed the entrepreneurial motivation of the Minang people. Even though the Minang people's creative process towards entrepreneurial success can be adopted as a source of value in developing entrepreneurial learning. This study aims to determine the values of the overseas Minangkabau community in entrepreneurship. To answer this question, qualitative research methods are used. Participants were 3 Minangkabau people who represented nomads who had successful entrepreneurship in Lampung province, information from research subjects was extracted through in-depth interviews. The data obtained were then analyzed descriptively qualitatively. The results of the data analysis were then examined using a motivational theory analysis knife. Obtained the value of self-esteem, the value of hard work and the value of contributing to the family as the motivation of overseas Minang people in entrepreneurship. In addition, the universal values extracted from the entrepreneurial culture can be used as a source of entrepreneurial value. It is suggested that further research can develop a Culturally Responsive Pedagogy Entrepreneurship.